Lenvatinib plus pembrolizumab in patients with advanced endometrial cancer: an interim analysis of a multicentre, open-label, single-arm, phase 2 trial. Issue 5 (May 2019) - Makker, Vicky; Rasco, Drew; Vogelzang, Nicholas J; Brose, Marcia S; Cohn, Allen L; Mier, James; Di Simone, Christopher; Hyman, David M; Stepan, Daniel E; Dutcus, Corina E; Schmidt, Emmett V; Guo, Matthew; et al.
Summary: Background: Lenvatinib is a multikinase inhibitor of VEGFR1, VEGFR2, and VEGFR3, and other receptor tyrosine kinases. Pembrolizumab, an antibody targeting PD-1, has moderate efficacy in biomarker-unselected endometrial cancer. We aimed to assess the combination of lenvatinib plus pembrolizumab in patients with advanced endometrial carcinoma, after establishing the maximum tolerated dose in a phase 1b study. Methods: In this open-label, single-arm, phase 2 study done at 11 centres in the USA, eligible patients were aged 18 years or older and had metastatic endometrial cancer (unselected for microsatellite instability or PD-L1), had an Eastern Cooperative Oncology Group performance status of 0 or 1, had received no more than two previous systemic therapies, had measurable disease according to the immune-related Response Evaluation Criteria In Solid Tumors (irRECIST), and had a life expectancy of 12 weeks or longer. Patients received 20 mg oral lenvatinib daily plus 200 mg intravenous pembrolizumab every 3 weeks. Treatment continued until disease progression, development of unacceptable toxic effects, or withdrawal of consent. The primary endpoint of this interim analysis was the proportion of patients with an objective response at week 24 as assessed by investigators according to irRECIST in the per-protocol population. This trial is registered withClinicalTrials.gov, numberNCT02501096 . Findings: Between Sept 10, 2015, and July 24, 2017, 54 patients were enrolled, 53 of whom were included in the analysis. At the cutoff date for anti-tumour activity data (Dec 15, 2017), median study follow-up was 13·3 months (IQR 6·7–20·1). 21 (39·6% [95% CI 26·5–54·0]) patients had an objective response at week 24. Serious treatment-related adverse events occurred in 16 (30%) patients, and one treatment-related death was reported (intracranial haemorrhage). The most frequently reported any-grade treatment-related adverse events were hypertension (31 [58%]), fatigue (29 [55%]), diarrhoea (27 [51%]), and hypothyroidism (25 [47%]). The most common grade 3 treatment-related adverse events were hypertension (18 [34%]) and diarrhoea (four [8%]). No grade 4 treatment-related adverse events were reported. Five (9%) patients discontinued study treatment because of treatment-related adverse events. Interpretation: Lenvatinib plus pembrolizumab showed anti-tumour activity in patients with advanced recurrent endometrial cancer with a safety profile that was similar to those previously reported for lenvatinib and pembrolizumab monotherapies, apart from an increased frequency of hypothyroidism. Lenvatinib plus pembrolizumab could represent a new potential treatment option for this patient population, and is being investigated in a randomised phase 3 study. Funding: Eisai and Merck.